A protocol for cell therapy infusion in neonates. (6th January 2021) - Baker, Elizabeth K.; Wallace, Euan M.; Davis, Peter G.; Malhotra, Atul; Jacobs, Susan E.; Hooper, Stuart B.; Lim, Rebecca
Abstract: Cell therapies for neonatal morbidities are progressing to early phase clinical trials. However, protocols for intravenous (IV) delivery of cell therapies to infants have not been evaluated. It has been assumed the cell dose prescribed is the dose delivered. Early in our clinical trial of human amnion epithelial cells (hAECs), we observed cells settling in the syringe and IV tubing used to deliver the suspension. The effect on dose delivery was unknown. We aimed to quantify this observation and determine an optimal protocol for IV delivery of hAECs to extremely preterm infants. A standard pediatric infusion protocol was modeled in the laboratory. A syringe pump delivered the hAEC suspension over 60 minutes via a pediatric blood transfusion set (200-μm filter and 2.2 mL IV line). The infusion protocol was varied by agitation methods, IV-line volumes (0.2-2.2 mL), albumin concentrations (2% vs 4%), and syringe orientations (horizontal vs vertical) to assess whether these variables influenced the dose delivered. The influence of flow rate (3-15 mL/h) was assessed after other variables were optimized. The standard infusion protocol delivered 17.6% ± 9% of the intended hAEC dose. Increasing albumin concentration to 4%, positioning the syringe and IV line vertically, and decreasing IV-line volume to 0.6 mL delivered 99.7% ± 13% of the intended hAEC dose. Flow rate did not affect dose delivery. Cell therapy infusion protocols must be considered. We describe the refinement of a cell infusion protocol that delivers intended cell doses and could form the basis of future neonatal cell delivery protocols. Abstract : Cell therapy is neonatal medicine's new frontier. While the challenges of translation have been much discussed, we have overlooked a simple yet fundamental hurdle; a protocol that delivers the intended cell dose intravenously to infants. Our existing protocol delivered less than 20% of the intended dose of human amnion epithelial cells. Here, we demonstrate simple measures can optimize cell dose delivery.